2022
DOI: 10.1039/d1nr06676e
|View full text |Cite
|
Sign up to set email alerts
|

Integrated osteochondral differentiation of mesenchymal stem cells on biomimetic nanofibrous mats with cell adhesion-generated piezopotential gradients

Abstract: Biomimetic piezoelectric scaffolds provide a noninvasive way for in vivo cell regulation and tissue regeneration. Herein, considering the gradually varied piezoelectric property of native cartilage and bone tissues, we fabricated...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…More interestingly, it has been found that PLGA scaffolds can regenerate both cartilage and subchondral bone tissues by simply adjusting the zonal-specific pore size or porosity of scaffolds [ 207 , 208 ]. Similarly, a recent study on poly( l -lactic acid) (PLLA), a stereoisomer of , evidenced that this material could support both osteogenic and chondrogenic differentiations upon the generation of a gradient piezoelectric field [ 209 ]. Although PLGA could promote cell activities, a study has shown that it also initiated de-differentiation of chondrocytes upon adhesion, and eventually led to the deposition of type I and type X collagen impurities in the neo-formed cartilage [ 23 ].…”
Section: Recent Biomaterials Selections For Fabrication Of Mzssmentioning
confidence: 99%
See 2 more Smart Citations
“…More interestingly, it has been found that PLGA scaffolds can regenerate both cartilage and subchondral bone tissues by simply adjusting the zonal-specific pore size or porosity of scaffolds [ 207 , 208 ]. Similarly, a recent study on poly( l -lactic acid) (PLLA), a stereoisomer of , evidenced that this material could support both osteogenic and chondrogenic differentiations upon the generation of a gradient piezoelectric field [ 209 ]. Although PLGA could promote cell activities, a study has shown that it also initiated de-differentiation of chondrocytes upon adhesion, and eventually led to the deposition of type I and type X collagen impurities in the neo-formed cartilage [ 23 ].…”
Section: Recent Biomaterials Selections For Fabrication Of Mzssmentioning
confidence: 99%
“…This can be achieved by prefabricating a support layer and then produce cell-derived layers to create a multilayered scaffold [ 23 , 319 ]. Alternatively, it can be simply realized by applying external forces such as DC electric field [ 209 ] or magnetic field [ 254 , 320 ] to redistribute the prefabricated uniformed constructs with gradient properties, forming a “fake” osteochondral MZS. Here the “fake” MZSs can be defined as those without obvious layered or gradient compositions and architectures but have gradient properties or bioactive signals from top-to-bottom of the spatial coordinates in the defect area to induce zonal-specific, chondrogenic/osteogenic differentiation and osteochondral regeneration.…”
Section: Novel Fabrications Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The flexibility of the polymer and the electromechanical coupling of the piezoelectric material makes the piezoelectric polymer attract unprecedented research enthusiasm in selfpowered wearable sensors [32], tissue scaffold [65], and energy conversion [66]. Nevertheless, a high-intensity electric field combined with hot stretching is conventionally required for the fabrication of polymeric piezoelectric films [67].…”
Section: Piezoelectric Polymers Andmentioning
confidence: 99%
“…These equations indicate that the enhancement of overall piezoelectric performance should focus on either increasing d or decreasing ε. Generally, the strategy of enhancing d is to increase the electroactive phase of the piezoelectric material [137,138] which is handily achieved by adjusting electrospinning parameters, such as electric field strength [65,139], solution concentration [140], thermal treatment [113], and drum collector rotating speed [141]. For example, Tai et al demonstrated that the nanofibrous PLLA web scaffold with finer fiber diameter was obtained via reducing the concentration of spinning solution.…”
Section: Current Challenges and Solutionsmentioning
confidence: 99%